Analisis Pengaruh Manajemen Laba dan Faktor Lainnya terhadap Nilai Perusahaan - Geraldine, Alani (Media Bisnis, 2024)
The aim of this research was to obtain empirical evidence that profit management and other factors, namely institutional ownership, managerial ownership, dividend policy, profitability, solvency, and liquidity affect the value of the company. This research used the population of consumer noncyclicals and consumer cyclicals companies listed on the Indonesia Stock Exchange for the period 2020 to 2022, a total sample used in the study of 60 companies. This research used purposive sampling method as sample selection method and used multiple regression method as data analysis method. The results of this research showed that profitability had a positive influence on firm value. On the other hand, profit management, institutional ownership, managerial ownership, dividend policy, solvency, and liquidity had no effect on firm value.